Changes in Quality of Life Score of Patients with Pelvic Organ Prolapse after Vaginal Surgery Measured by Pelvic Floor Distress Inventory (PFDI20) and Pelvic Floor Impact Questionnaire (PFIQ7) Questionnaires - Hakim, Surahman; Maharani, Cut R (Indonesian Socety of Obstetrics and Gynecology, 2017)
Objective: To determine changes in the quality of life in patients with pelvic organ prolapse who had undergone vaginal surgery. Methods: Prospective cohort study, carried out in Dr. Cipto Mangunkusumo and Fatmawati during the period of July 2015 to October 2016. The quality of life of the subjects was followed up three months after undergoing vaginal surgery. We used the Indonesian version of Pelvic Floor Distress Inventory (PFDI-20) and Pelvic Floor Impact Questionnaire (PFIQ-7). Results: In this study, 25 subjects were involved. The results showed significant score reduction in the quality of life in patients treated with vaginal surgery with p < 0.05 in almost all scales except CRAIQ-7. Conclusion: There is a reduction in quality of life scores in patients treated with vaginal surgery at all scales except CRAIQ-7 with a value of p <0.05. [Indones J Obstet Gynecol 2017; 5-3: 164-167] Keywords: PFDI-20, PFIQ-7, POP, vaginal surgery